The role of C-black in improvement of tribological properties of industrial rubber materials (Deproteinised Natural Rubber and polyisoprene) - El-Tayeb, N. S. M, N. S. M; Nasir, R. Md (2005)
This is a part of collaborative project between Multimedia University, Melaka and Malaysia Rubber Board, Sg. Buloh, Selangor. In this work, the tribological properties of Deproteinised Natural Rubber (DPNR) was examined and compared with synthetic cis 1,4 polyisoprene rubber (IR) namely Natsyn 2200. The effect of adding carbon black (CB) (0, 25 and 50 phr) to both DPNR and IR on the friction and wear characteristics was investigated. Dry abrasion tests were carried out using pin-on-ring tribometer with abrasive paper (diamond-50) under different operating test conditions such as applied normal load (5-35N), sliding speed (0.3-1.5 m/s), and sliding distance (90-450m).